Modelos conceituais de dados como parte do processo da catalogação: perspectiva de uso dos FRBR no desenvolvimento de catálogos bibliográficos digitais - Fusco, Elvis [UNESP] (2010)
The cataloguing process is aimed at dealing with bibliographic registers as information support, serving as a basis for an interoperability among information environments, taking into account different objects and cooperative and heterogeneous basis. Among the main propositions of the cataloguing field are the FRBR - Functional Requirements for Bibliographic Records, which constitute of new concepts in cataloguing standards. These standards indicate access to the rearrangement of bibliographic registers in order to reflect on the conceptual framework of persistence and search of information, considering the diversity of users, material, physical support, and formats. In this context, the present research is aimed at reflecting and discussing, from a conceptual architecture, logic and information environment persistence based on FRBR and Entity-Relationship Modeling and extended by the use of concepts of Object Orientation, the process of cataloguing in the context of the catalogs project by using computation methodology of Data Conceptual Modeling, considering the evolution of this area in the scope of Information Science in relation to the context of the representation of information aiming use and interoperability of every and each information resource to fill the lack between the conceptual project of an application domain and the definition of the metadata scheme of bibliographic registers structures. Thus, this research defends the necessity and urgency to review the cataloguing process adding the elements of Computing Science with the use of Information Descriptive Treatment methodologies in the scope of the information representation in the layer of persistence of an automated information environment. The research issue is based in the presupposition of the existence in a relation of community among... (Complete abstract click electronic access below)